Subsidy Mechanism for Rail Transit Renewal and Renovation in Japan and the Enlightenment to China - CHEN Yan; LIU Yachen; CHENG Yan; ZHAO Huawei; YANG Jun (Chengshi guidao jiaotong yanjiu)
［Objective］ Drawing on the successful experiences of Japanese government in promoting the rail transit through subsidies can provide relevant cases of practical guiding significance for the establishment of an effective governmental subsidy mechanism in China at the stage of urban rail transit renewal and renovation. ［Method］ The rail transit-related subsidy systems successively introduced by Japan after the 1960s are taken as the research objects, and according to different business forms of Japan′s rail transit undertakings, Japan′s current subsidy systems are divided into four categories for urban railways, trunk railways, safety, disaster prevention and technology development, which have constituted a complete and systematic auxiliary mechanism. The subsidy purpose, subsidy objects and subsidy contents are studied and analyzed, and the subsidy management institutions and the subsidy procedures are introduced. ［Result & Conclusion］ Finally, combined with the realities in China, it is suggested that a financial subsidy system should be established for the renovation of existing lines, the management system be improved, and dynamic evaluation and adjustment be implemented.